Response to chemical and organic fertilization in date palm (Phoenix dactylifera L.) Mejhoul variety in Northwestern Mexico (Agro Productividad, 2024)
This research was conducted to determine the effect of chemical, organic, and combined fertilization on the fruit yield of the Mejhoul date palm variety in Northwestern of Mexico. The variables measured were polar diameter, equatorial diameter of the fruit, roundness index, number of clusters, number of leaves per palm, number of leaves per cluster, fruits with separated skin, dried fruits and commercial yield. The design used was complete randomized blocks with five replicates, where each palm tree was the experimental unit. The results indicate that chemical fertilization 262N-138P2O5-540K2O alone or in combination with compost application (three or six tons per hectare) increases polar and equatorial diameter, promoting the oval growth of dates. Fruits with separated skin continue to occur regardless of the origin of the fertilizers. The number of fruits increases with chemical fertilization, but the total yield of dates remains consistent across the treatments evaluated. In conclusion, date palms respond favorably to the combination of chemical and organic fertilization, but date yields did not increase.